تكامل التعلم العميق في منهج اللغة العربية: التوقعات والتحديات - Suryani, Ria Rafita (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
Arabic language education in Indonesia is still largely dominated by traditional teacher-centered approaches, rendering it less compatible with the demands of the 21st century. Within the context of national educational reform, the concept of deep learning-which emphasizes mindful, meaningful, and joyful learning-has been introduced as an innovative alternative. This study aims to explore the potential and challenges of integrating deep learning into the Arabic language curriculum in Indonesia. This research employs a library-based method by analyzing academic literature related to the application of deep learning in language education. The findings indicate that implementing deep learning in Arabic instruction can enhance student engagement, deepen conceptual understanding, and create a more interactive and enjoyable learning environment. However, this integration faces several challenges, including limited technological infrastructure, insufficient teacher readiness, diverse student characteristics, and reliance on conventional assessment systems. The study concludes that deep learning holds significant potential to transform Arabic language education in Indonesia. Nevertheless, its success depends heavily on the overall preparedness of the educational system. The implications highlight the importance of teacher training, digital resource development, and assessment reform to support sustainable pedagogical transformation.